In my skin : my life on, and off, the basketball court - Griner, Brittney; Hovey, Sue (It Books, an imprint of HarperCollins Publishers, 2014)
Griner, the dunking phenom and national sensation who is shattering stereotypes and breaking boundaries, now shares her coming-of-age story, revealing how she found her strength to overcome bullies and to embrace her authentic self. Possessing a combination of size and athleticism never before seen in women's basketball, she is equally famous for making headlines off the court, for speaking out on issues of gender, sexuality, body image and self-esteem. The Phoenix Mercury star has heard every vicious insult in the book, enduring years of taunting that began in middle school and continues to this day, but has learned to remain true to herself, rising above the haters trying to take her down.